Insights into the Future Control Strategy of Plant Viruses from a Model Pathosystem - Komatsu Ken; Arie Tsutomu; Novianti Fawzia (E3S Web of Conferences)
Plant diseases threaten global crop production. Among plant disease pathogens, viruses are the most difficult to control because there are no chemical measures that can directly limit their infection. To develop novel strategies to control plant viruses, we need to understand how they infect plants and cause symptoms. We have been investigating the mechanisms underlying plant-virus interactions using plantago asiatica mosaic virus (PlAMV), a mechanically transmitted RNA virus that causes necrosis in ornamental lilies worldwide, and can infect two important model plant hosts Arabidopsis thaliana and Nicotiana benthamiana. Recent findings include the genetic diversity of PlAMV, the identification of the membrane-associated domain of the PlAMV replicase, and the inhibitory effects of a plant immune activator against PlAMV infection. These findings will provide us with insight into the future control of plant viruses.